ANALISIS DAMPAK PELABUHAN POMAKO TERHADAP SEKTOR EKONOMI DI KAMPUNG POMAKO KABUPATEN MIMIKA - ludia payung; Tiurlina Siregar; Enos H Rumansara (Magister Perencanaan Wilayah dan Kota Universitas Cenderawasih, 2021)
The port is a vital infrastructure needed by a region to provide convenience in the process of entering and leaving goods and also people from and out of the region. The benefits of port infrastructure can directly improve the regional economy because it helps various sectors in the region in terms of logistics supply. The purpose of this research is to see the impact of the existence of the Pomako port on changes in the economic order in the surrounding area and to examine the potential of vacant land around the Pomako port area to be converted into a functional land that supports the development of the trade, tourism and industry sectors. The method used in this research is descriptive analysis of the results of observations, interviews and documentation studies. The results obtained are that the Pomako port has a positive impact in the form of economic growth in the Mimika Timur district of Mimika Regency.